2012
DOI: 10.1104/pp.112.199257
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NRT1.5 Is Another Essential Component in the Regulation of Nitrate Reallocation and Stress Tolerance  

Abstract: Nitrate reallocation to plant roots occurs frequently under adverse conditions and was recently characterized to be actively regulated by Nitrate Transporter1.8 (NRT1.8) in Arabidopsis (Arabidopsis thaliana) and implicated as a common response to stresses. However, the underlying mechanisms remain largely to be determined. In this study, characterization of NRT1.5, a xylem nitrate-loading transporter, showed that the mRNA level of NRT1.5 is down-regulated by salt, drought, and cadmium treatments. Functional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
177
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(190 citation statements)
references
References 47 publications
9
177
2
2
Order By: Relevance
“…Expression of the two genes is influenced by NO 3 2 concentration. NRT1.5 is strongly induced by NO 3 2 (Lin et al, 2008), while NRT1.8 expression is extremely up-regulated in nrt1.5 mutants (Chen et al, 2012). A negative correlation between the extents of expression of the two genes was observed when plants are subjected to abiotic stresses (Chen et al, 2012).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Expression of the two genes is influenced by NO 3 2 concentration. NRT1.5 is strongly induced by NO 3 2 (Lin et al, 2008), while NRT1.8 expression is extremely up-regulated in nrt1.5 mutants (Chen et al, 2012). A negative correlation between the extents of expression of the two genes was observed when plants are subjected to abiotic stresses (Chen et al, 2012).…”
mentioning
confidence: 97%
“…A previous study showed that increased NRT1.8 expression in nrt1.5 mutants (Chen et al, 2012) and the expression of NRT1.5 was induced by NO 3 2 (Lin et al, 2008). We tested the relationship between NRT1.5 and NRT1.8 expression in Arabidopsis and B. napus.…”
Section: Nomentioning
confidence: 99%
See 3 more Smart Citations